PENGARUH MODEL FLIPPED CLASSROOMDAN SIKAP SISWA TERHADAP HASIL BELAJAR EKONOMI - Widytia Pharamitha; Bustari Muchtar (Jurnal Kajian Pendidikan Ekonomi, 2016)
This research was to contruct: 1) the effect of flipped classroom learning model through the student result study, 2) the sffect of students behaviour  through the student result study, 3) The interaction between the learning model through the student behaviour. The planng of the recearch was using quosy experiment. Sample of the recearchwas taken by using purposive sampling. The data collected by questionaire and student answerstest they areanayzed descriptively and inductively by using ANOVA.  The result of the reserch were: 1) student who using flipped calssroom model in the learning process showed the good result in economic subject, 2) the student who have the positive behavior in the learning process showed the good result, 3) there were no interaction betwen the using of this learning model though the student behavior in the , economic result. Keywords: flipped classroom model, behaviour, economic result